Primary myxofibrosarcoma of the male breast: A case report - Achouri, Leila; Jouini, Safa; Mansouri, Houyem; Chaabouni, Salma; Henchiri, Houda; Mahjoub, Najet (Indian Journal of Case Reports, 2024)
Myxofibrosarcoma is an unusual type of malignant fibrous histiocytoma that arises in subcutaneous tissue in the limbs of elderly patients and uncommonly involves the breast. We report a rare case of myxofibrosarcoma that occurred in a male breast. A 57-year-old man was referred to our department for a right breast mass. Physical examination revealed an irregular lump without skin involvement. Ultrasonography and mammography showed an oval and hypoechoic opacity with increased internal vascularity. The patient had a core needle biopsy that showed a sarcoma of the breast. The patient underwent a simple mastectomy. The pathology report confirmed the diagnosis of high-grade myxofibrosarcoma of the breast and the patient had local radiotherapy. After a follow-up of 18 months, the patient has no evidence of local recurrence or distant metastases. Myxofibrosrcoma of the breast is extremely rare but should be diagnosed as soon as possible because of the rapid growth of the tumor and the better prognosis in the early stages.